2018
DOI: 10.14236/ewic/hci2018.148
|View full text |Cite
|
Sign up to set email alerts
|

A Hindi Virtual Keyboard Interface with Multimodal Feedback: A Case Study with a Dyslexic Child

Abstract: Up to 15% of the Indian school-going children suffer from dyslexia. This paper aims to determine the extent to which existing knowledge about the eye-tracking based human-computer interface can be used to assist these children in their reading and writing activities. A virtual keyboard system with multimodal feedback is proposed and designed for a lexically and structurally complex language and optimized for multimodal feedback involving several portable, non-invasive, and low-cost input devices: a touch scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the ETSS modality, the eye-tracker was used for pointing to the item that can be then selected by pressing the soft-switch. HCI modalities include two visual (positive and negative feedback) and one auditory feedback (beep after successful execution of each command) [12]. In the gaze-based VK application, efficient feedback is necessary for the user so that the intended command box/character was selected to avoid errors in copy spelling and increase efficiency [22].…”
Section: B Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ETSS modality, the eye-tracker was used for pointing to the item that can be then selected by pressing the soft-switch. HCI modalities include two visual (positive and negative feedback) and one auditory feedback (beep after successful execution of each command) [12]. In the gaze-based VK application, efficient feedback is necessary for the user so that the intended command box/character was selected to avoid errors in copy spelling and increase efficiency [22].…”
Section: B Modalitiesmentioning
confidence: 99%
“…Dyslexic readers of the Hindi language have a complication in developing highquality, segmentally organized phonological representations of words and display poor blending skills [11]. While a pilot study suggested the possibility to enhance the awareness of a child with dyslexia through an adaptive multimodal interface using eye-tracking [12], this trend needs to be demonstrated rigorously with a collection of children with dyslexia and a control group, as proposed in this paper.…”
Section: Introductionmentioning
confidence: 98%
“…Other dwell-free techniques include multimodal and hybrid interfaces. These techniques address issues highlighted in previous studies [18,[42][43][44][45][46][47][48]. In particular, these studies have introduced a dwell-free technique for an eye-typing system, which focused on a combination of different modalities such as eye-tracking, smiling movements, input switches, and speech recognition.…”
Section: Introductionmentioning
confidence: 95%